Undernutrition in childhood resulted in bad dietary behaviors and the increased risk of hypertension in a middle-aged Chinese population. (1st June 2018) - Zhang, L.; Sheng, J.; Xuan, Y.; Xuan, P.; Zhou, J.; Fan, Y.; Zhu, X.; Liu, K.; Yang, L.; Tao, F.; Wang, S.
Abstract: This study was designed to explore the association between undernutrition in the growth period and cardiovascular risk factors in a middle-aged Chinese population. A total of 1756 subjects, aged 45–60 years, were invited to participate in the Hefei Nutrition and Health Study and divided into three groups according to their self-reported animal food intake in the growth period. Group 1, Group 2 and Group 3 were defined as undernutrition, nutritional improvement and the good nutrition group, respectively. In the three groups, the subjects in Groups 1 and 2 had more oil and salt intake ( P <0.001), and less eggs and milk intake ( P <0.001), when compared with the subjects in Group 3. After adjusting for age, education, smoking status and other confounding factors, it was found that male participants who experienced nutritional improvement before age 18 had higher risk of hypertension [odds ratio (OR)=1.68; 95% confidence intervals (CI): 1.05, 2.69] than those with good nutrition, and female participants with undernutrition (OR=1.52; 95% CI: 1.01, 2.29) and nutritional improvement (OR=1.68; 95% CI: 1.04, 2.69) before age 18 had a higher risk of hypertension than those with good nutrition. For diabetes, obesity, hypercholesterolemia and hypertriglyceridemia, our results did not found difference among the three groups both in male and female. Our findings indicated that nutritional deficiency in childhood was associated with bad dietary behaviors and a significantly increased risk of hypertension in middle age. Therefore, early adequate nutrition is very important for the prevention of non-communicable diseases later.